Development of The Interactive Learning Media Based on Augmented Reality 3D on The Petroleum Concept - Sultan Fakhrur Rassyi Rassyi; Supriadi; Yayuk Andayani; Aliefman Hakim; Burhanuddin; Saprizal Hadisaputra (Universitas Islam Indonesia, 2023)
Chemistry is studied by students at the high school level. However, due to the abstract concept of chemistry, chemistry becomes difficult for some students to learn. One problem with studying chemistry is the petroleum material in online and offline learning systems. This study aimed to determine the feasibility and practicality of interactive learning media based on the 3D augmented reality of petroleum topics. This study aims to describe the making of applications with augmented reality technology as a medium for learning chemistry. The research type was development research that adopted a 4D model (define, design, develop, disseminate) but was limited to the development stage. The population in this study was 192 students of public high school SMAN 7 Mataram, Indonesia. This study's sampling was carried out using a random sampling technique measured through an expert validation sheet with three assessment aspects assessed by three validators. The practicality level of the media was measured through a practicality questionnaire filled out by 22 students in eleventh-grade students at SMAN 7 Mataram. The results showed that the validator assessed media feasibility was 90.16%, which indicated that the media developed was very feasible. Meanwhile, the media practicality test results revealed that students responded positively to all media components with a practicality percentage of 94.39%. In conclusion, the media developed is feasible and practical to use.